Electrocoagulation Therapy for Urethral Condyloma Acuminata in a Male Patient: Case Report - Ghassane El Omri; Hamza Rais; Anas Taghouan; Moussaab Rachid; Younes Houry; Abdeljalil Heddat (Clinical Medicine Insights: Case Reports)
Condyloma acuminata (CA) is a common manifestation of human papillomavirus (HPV) infection affecting the urogenital tract. While external genital lesions are frequently encountered, urethral involvement presents a therapeutic challenge due to the risk of recurrence and long-term complications such as urethral stricture. We present a case of urethral condyloma acuminata in a 43-year-old male patient who demonstrated favorable progression following electrocoagulation therapy. The patient presented with urethrorrhagia and lower urinary tract symptoms, with subsequent diagnosis confirmed via urological examination. Negative results from extensive microbiological testing supported the diagnosis. Treatment involved biopsy excision combined with electrocoagulation, resulting in complete resolution of symptoms without recurrence at 2-month follow-up. This case underscores the importance of individualized treatment strategies for intraurethral condyloma acuminata and highlights electrocoagulation therapy as a viable option with favorable outcomes.